Effect of Weight Loss after Bariatric Surgery on Thyroid-Stimulating Hormone Levels in Patients with Morbid Obesity and Normal Thyroid Function - Neves, JS (2018)
Background: Several studies have reported that morbid obesity is associated with increased thyroid-stimulating hormone (TSH) levels. However, it is not clear what is the impact of bariatric surgery on postoperative thyroid function. The aim of this study was to evaluate the effect of weight loss after bariatric surgery on TSH levels in euthyroid patients with morbid obesity. Methods: We performed a retrospective observational study of 949 euthyroid patients (86.1% female; age 42.0 ± 10.3 years, BMI 44.3 ± 5.7 kg/m2) with morbid obesity submitted to bariatric surgery (laparoscopic adjustable gastric band, Roux-en-Y gastric bypass, or sleeve gastrectomy). Patients were subdivided in two groups: normal TSH group (TSH <2.5 mU/L) and high-normal TSH group (TSH ≥2.5 mU/L). The impact of anthropometric parameters, comorbidities, TSH, free thyroxine (FT4), free triiodothyronine (FT3), type of surgery, and excessive body weight loss (EBWL) on TSH variation 12 months after surgery was evaluated. Results: The high-normal TSH group (24.3% of patients) included more women, presented a higher BMI, higher systolic blood pressure, and higher FT3 levels. There was a significant decrease of TSH 12 months after surgery that was more marked in the high-normal TSH group (normal TSH group: 1.57 ± 0.49 to 1.53 ± 0.69 mIU/L, p = 0.063; high-normal TSH group: 3.23 ± 0.59 to 2.38 ± 0.86 mIU/L, p < 0.001). In a multivariate analysis, after adjusting for relevant covariates, EBWL, baseline BMI, and baseline FT3 were significantly associated with TSH decrease 12 months after bariatric surgery. Conclusion: Bariatric surgery promotes a decrease of TSH that is significantly greater in patients with high-normal TSH and is independently associated with EBWL after surgery.